Soluble T Cell Immunoglobulin Mucin Domain 3 Is Shed from CD8 + T Cells by the Sheddase ADAM10, Is Increased in Plasma during Untreated HIV Infection, and Correlates with HIV Disease Progression - Clayton, Kiera L.; Douglas-Vail, Matthew B.; Rahman, A. K. M. Nur-ur; Medcalf, Karyn E.; Xie, Irene Y.; Chew, Glen M.; Tandon, Ravi; Lanteri, Marion C.; Norris, Philip J.; Deeks, Steven G.; Ndhlovu, Lishomwa C.; Ostrowski, Mario A. (Journal of virology, 2015)
Chronic HIV infection results in a loss of HIV-specific CD8 + T cell effector function, termed “exhaustion,” which is mediated, in part, by the membrane coinhibitory receptor T cell immunoglobulin mucin domain-3 (Tim-3). Like many other receptors, a soluble form of this protein has been described in human blood plasma. However, soluble Tim-3 (sTim-3) is poorly characterized, and its role in HIV disease is unknown. Here, we show that Tim-3 is shed from the surface of responding CD8 + T cells by the matrix metalloproteinase ADAM10, producing a soluble form of the coinhibitory receptor. Despite previous reports in the mouse model, no alternatively spliced, soluble form of Tim-3 was observed in humans. Shed sTim-3 was found in human plasma and was significantly elevated during early and chronic untreated HIV infection, but it was not found differentially modulated in highly active antiretroviral therapy (HAART)-treated HIV-infected subjects or in elite controllers compared to HIV-uninfected subjects. Plasma sTim-3 levels were positively correlated with HIV load and negatively correlated with CD4 counts. Thus, plasma sTim-3 shedding correlated with HIV disease progression. Despite these correlations, we found that shedding Tim-3 did not improve the function of CD8 + T cells in terms of gamma interferon production or prevent their apoptosis through galectin-9. Further characterization studies of sTim-3 function are needed to understand the contribution of sTim-3 in HIV disease pathogenesis, with implications for novel therapeutic interventions. IMPORTANCE Despite the overall success of HAART in slowing the progression to AIDS in HIV-infected subjects, chronic immune activation and T cell exhaustion contribute to the eventual deterioration of the immune system. Understanding these processes will aid in the development of interventions and therapeutics to be used in combination with HAART to slow or reverse this deterioration. Here, we show that a soluble form of T cell exhaustion associated coinhibitory molecule 3, sTim-3, is shed from the surface of T cells. Furthermore, sTim-3 is elevated in the plasma of treatment-naive subjects with acute or chronic HIV infection and is associated with markers of disease progression. This is the first study to characterize sTim-3 in human plasma, its source, and mechanism of production. While it is still unclear whether sTim-3 contributes to HIV pathogenesis, sTim-3 may represent a new correlate of HIV disease progression.